Effect of Financial Management Practices on Students’ Academic Performance in Public Secondary Schools in Machakos Sub- County, Machakos County, Kenya - Ndunda, Tiffany Ndanu; Mulwa, David M.; Muriungi, Pamella Karambu (IOSR Journal of Humanities and Social Science (IOSR-JHSS), 2025)
The interest in school leadership is based on the belief it can significantly influence directly or indirectly, the teaching and quality of learning in schools, and as a result student achievement. This study investigated the effect of financial management practices on students’ academic performance in public secondary schools in Machakos Sub-County, Machakos County, Kenya. The study was based on the prudential theory. A descriptive research design was used for this study. The target population for this study were 48 principals and 400 teachers totalling 448 respondents from which a sample of 15 principals and 120 teachers were chosen using simple random sampling. Questionnaires were used to collect data from the respondents. Validity was established through expert judgment. The research used Cronbach's alpha formula to test reliability. Cronbach’s alpha coefficient of 0.9641 was realized indicating the consistency of research instruments. Data collected were coded and analysed with the help of the Stata analysis package. Descriptive statistics in the form of mean and standard deviation were used to display the data. Inferential statistics specifically regression analysis was used to show the relationship and strength of the relationships among study variables respectively. The study found that financial management practices had a positive and statistically significant effect on students’ academic performance. Based on the findings, the study recommends that there is a need for the principal to have good administrative financial skills, ensure the bazaar office provides full accounting reports on time, allow students to continue learning even though they have fee arrears, and ensure all the accounts records are well kept
Keywords: Financial Management Practices; Students’ Academic Performance; Public Secondary Schools